2010
DOI: 10.1007/s12115-010-9349-8
|View full text |Cite
|
Sign up to set email alerts
|

The Next Big Thing: Local Celebrity

Abstract: In this essay I observe that, as the field of celebrity studies established itself in the academy, there is a need for a distinctly sociological and interactional approach to celebrity. In particular, I argue for a focus on the experiential and relational dynamics of celebrity from the point of view of celebrities themselves, something which has so far been difficult for researchers to achieve. One way to accomplish this goal is to move in the direction celebrity itself seems to be headed: toward local or subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 13 publications
0
31
0
2
Order By: Relevance
“…It is recommended that farmers and ranchers be instructed on how to deliver their personal stories effectively to LEOs. Further, farmers and ranchers could be considered local celebrities (Ferris, 2010) and, therefore, have the potential to serve as a heuristic that expidites the decision-making process for LEOs. To prepare farmers or ranchers to communicate with county commissioners, they should be instructed on how to frame the information in a way that demonstrates how the proposed policy could negatively or positively impact them as a member of the ANR community.…”
Section: Objective Four: County Commissioners' Preferred Methods Of Bmentioning
confidence: 99%
“…It is recommended that farmers and ranchers be instructed on how to deliver their personal stories effectively to LEOs. Further, farmers and ranchers could be considered local celebrities (Ferris, 2010) and, therefore, have the potential to serve as a heuristic that expidites the decision-making process for LEOs. To prepare farmers or ranchers to communicate with county commissioners, they should be instructed on how to frame the information in a way that demonstrates how the proposed policy could negatively or positively impact them as a member of the ANR community.…”
Section: Objective Four: County Commissioners' Preferred Methods Of Bmentioning
confidence: 99%
“…Celebrity preferences are further related to cultural proximity (Tian and Hoffner, 2010), here defined as "the tendency to prefer media products from one's own culture or the most similar possible culture" (Straubhaar, 2003, p. 85). This concept is relevant in a globalizing celebrity and media culture where audiences are faced with global and local celebrities (Ferris, 2010;Turner, 2004). De Backer, Nelissen, Vyncke, Braeckman, and McAndrew (2007) found that younger people prefer American celebrities, admiring their glamour, while older people connect to local celebrities.…”
Section: Celebrities: Parasocial Interaction Versus Parasocial Relatimentioning
confidence: 99%
“…The first is Kerry Ferris (2007), an American sociologist who specialises in ethnographic research on celebrity, including local celebrities (Ferris 2004(Ferris , 2010. She observed two dominant strands within the literature on celebrity: celebrity and celebrity worship as a pathology (e.g., McCutcheon et al 2002) and critical thinking on celebrity as a cultural commodity (King 2010, Marshall 1997.…”
Section: Trends and Challenges In Celebrity Studies Researchmentioning
confidence: 99%
“…Finally, Ferris (2010) suggested another approach to enhance the likelihood of gaining access to celebrity respondents. Instead of conducting research on the so-called A-list celebrities with international allure, she focused on local celebrities such as anchors of local TV news stations.…”
Section: P 955)mentioning
confidence: 99%